Human cytomegalovirus UL23 exploits PD-L1 inhibitory signaling pathway to evade T cell-mediated cytotoxicity - Qin Yuan; Zhaosong Fan; Wenqiang Huang; Xiaoping Huo; Xiaoping Yang; Yanhong Ran; Jun Chen; Hongjian Li (mBio, 2024)
ABSTRACT Human cytomegalovirus (HCMV), a widely prevalent human beta-herpesvirus, establishes lifelong persistence in the host following primary infection. In healthy individuals, the virus is effectively controlled by HCMV-specific T cells and typically exhibits asymptomatic. The T cell immune response plays a pivotal role in combating HCMV infection, while HCMV employs various strategies to counteract it within the host. Previously, we reported that UL23, a tegument protein of HCMV, facilitates viral immune evasion from interferon-gamma (IFN-γ) responses, and it is well known that IFN-γ is mainly derived from T cells. However, the involvement of UL23 in viral immune evasion from T cell-mediated immunity remains unclear. Herein, we present compelling evidence that UL23 significantly enhances viral resistance against T cell-mediated cytotoxicity during HCMV infection from the co-culture assays of HCMV-infected cells with T cells. We found that IFN-γ plays a major role in regulating T cell cytotoxicity mediated by UL23. More interestingly, we demonstrated that UL23 not only regulates the IFN-γ downstream responses but also modulates the IFN-γ secretion by regulating T cell activities. Further experiments indicate that UL23 upregulates the expression and signaling of programmed death ligand 1 (PD-L1), which is responsible for inhibiting multiple aspects of T cell activities, including activation, apoptosis, and IFN-γ secretion, as determined through RNA-seq analysis and inhibitor-blocking experiments, ultimately facilitating viral replication and spread. Our findings highlight the potential role of UL23 as an alternative antagonist in suppressing T cell cytotoxicity and unveil a novel strategy for HCMV to evade T cell immunity.IMPORTANCET cell immunity is pivotal in controlling primary human cytomegalovirus (HCMV) infection, restricting periodic reactivation, and preventing HCMV-associated diseases. Despite inducing a robust T cell immune response, HCMV has developed sophisticated immune evasion mechanisms that specifically target T cell responses. Although numerous studies have been conducted on HCMV-specific T cells, the primary focus has been on the impact of HCMV on T cell recognition via major histocompatibility complex molecules. Our studies show for the first time that HCMV exploits the programmed death ligand 1 (PD-L1) inhibitory signaling pathway to evade T cell immunity by modulating the activities of T cells and thereby blocking the secretion of IFN-γ, which is directly mediated by HCMV-encoded tegument protein UL23. While PD-L1 has been extensively studied in the context of tumors and viruses, its involvement in HCMV infection and viral immune evasion is rarely reported. We observed an upregulation of PD-L1 in normal cells during HCMV infection and provided strong evidence supporting its critical role in UL23-induced inhibition of T cell-mediated cytotoxicity. The novel strategy employed by HCMV to manipulate the inhibitory signaling pathway of T cell immune activation for viral evasion through its encoded protein offers valuable insights for the understanding of HCMV-mediated T cell immunomodulation and developing innovative antiviral treatment strategies.